USE OF AUTHENTIC FILMS WITH SUBTITLES IN THE PROCESS OF LEARNING NEW VOCABULARY IN HIGHER EDUCATION SECTOR (AS BASED ON THE ENGLISH LANGUAGE MATERIAL) - Anna S. Fomichenko (Sovremennye Issledovaniâ Socialʹnyh Problem, 2022)
Background. Watching movies with subtitles is a significant tool when learning English, as it is as close as possible to the language reality. The video contains visual images and the necessary audio material, which makes the process of memorizing new vocabulary effective and easy. This work is aimed at identifying the features of using authentic films with subtitles, in particular, at acquiring and enriching the vocabulary of students.